2010
DOI: 10.1016/j.apergo.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sinusoidal rolling ground motion on lifting biomechanics

Abstract: The objective of this study was to quantify the effects of ground surface motion on the biomechanical responses of a person performing a lifting task. A boat motion simulator (BMS) was built to provide a sinusoidal ground motion (simultaneous vertical linear translation and a roll angular displacement) that simulates the deck motion on a small fishing boat. Sixteen participants performed lifting, lowering and static holding tasks under conditions of two levels of mass (5 and 10kg) and five ground moving condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 18 publications
(26 reference statements)
1
10
0
Order By: Relevance
“…The EMG surface electrodes were placed on the skin, based on SENIAM 5, Mega Manual and Mega Win Software, over erector spinae, anterior deltoid, biceps brachii, and trapezius on the dominant side of the participant. Similar muscle groups were chosen in lifting studies by Keir et al (2011), andNing andMirka (2010). The EMG signals were recorded using the average mode and time interval of 0.1s (Ramadan and Al-Shayea, 2013).…”
Section: Emg Instrumentmentioning
confidence: 99%
“…The EMG surface electrodes were placed on the skin, based on SENIAM 5, Mega Manual and Mega Win Software, over erector spinae, anterior deltoid, biceps brachii, and trapezius on the dominant side of the participant. Similar muscle groups were chosen in lifting studies by Keir et al (2011), andNing andMirka (2010). The EMG signals were recorded using the average mode and time interval of 0.1s (Ramadan and Al-Shayea, 2013).…”
Section: Emg Instrumentmentioning
confidence: 99%
“…In addition, severe ankle stress and imbalance was reported by several participants on the 30 o slope. The existing study suggests that the increase of multifidus' activities can help elevate spinal stability (Ning et al, 2010). This was validated by video observation results.…”
Section: Chapter Discussionsupporting
confidence: 53%
“…Another study which investigated the effects of ground rolling motion on bilateral low back muscle activity during weight lifting on a simulated boat demonstrated clear differences between the bilateral trunk extensor muscles with the lateral angular displacement of the ground surface (Ning & Mirka, 2010). In the same study, an elevated trunk muscle co-contraction was also observed which has been shown to increase spinal loading (Granata & Marras, 1995) thereby elevate the risk of LBP (Neumann et al, 1999).…”
Section: Uneven Ground and Musculoskeletal Disordersmentioning
confidence: 86%
“…Figure 2 lists most common construction tasks and a majority of those are related with uneven working surface and high MSDs incidence rate ( Figure 2). In addition, agriculture industry (Zhao et al, 1987), fishing industry (Ning & Mirka, 2010;Mirka et al, 2011) and transportation industry (Andres et al, 2005) also involve substantial amount of uneven working surface.…”
Section: Uneven Ground In Occupational Environmentmentioning
confidence: 99%